Purified Graphene Oxide Dispersions Lack In Vitro Cytotoxicity and In Vivo Pathogenicity. Issue 3 (4th October 2012) - Ali‐Boucetta, Hanene; Bitounis, Dimitrios; Raveendran‐Nair, Rahul; Servant, Ania; Van den Bossche, Jeroen; Kostarelos, Kostas
Abstract Prompted by the excitement from the description of single layer graphene, increased attention for potential applications in the biomedical field has been recently placed on graphene oxide (GO). Determination of the opportunities and limitations that GO offers in biomedicine are particularly prone to inaccuracies due to wide variability in the preparation methodologies of GO material in different laboratories, that results in significant variation in the purity of the material and the yield of the oxidation reactions, primarily the Hummers method used. Herein, the fabrication of highly pure, colloidally stable, and evenly dispersed GO in physiologically‐relevant aqueous buffers in comparison to conventional GO is investigated. The purified GO material is thoroughly characterized by a battery of techniques, and is shown to consist of single layer GO sheets of lateral dimensions below 500 nm. The cytotoxic impact of the GO in vitro and its inflammation profile in vivo is investigated. The purified GO prepared and characterized here does not induce significant cytotoxic responses in vitro, or inflammation and granuloma formation in vivo following intraperitoneal injection. This is one of the initial steps towards determination of the safety risks associated with GO material that may be interacting with living tissue.